Media Interaktif dan Power Point terhadap Motivasi dan Hasil Belajar Anatomi Fisiologi Mahasiswa - Suharti Suharti; Daryono Daryono; Abbasiah Abbasiah; Dewi Masyitah (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the effect of interactive media and motivation on anatomy and physiology learning outcomes in health polytechnic students of the Jambi obstetrics department. This research method is quasi-experimental, using a pre-test, post-test control group design. The results showed that the pre-test value of the experimental class group was 2238, with an average value of 74.60 with a standard deviation of 3.024. While the post-test in this practical class obtained a total of 2373, the average value was 79.10 with a standard deviation of 3.736. Meanwhile, the total pre-test score for the control group was 2000, with an average score of 66.67 with a standard deviation of 5.287. At the same time, the post-test in the control class obtained a total score of 2112 and an average value of 70.40 with a standard deviation of 7.700. In conclusion, there is an effect of using interactive media and motivation to increase learning outcomes of anatomy and physiology of Jambi Health Polytechnic students, Department of Midwifery. Keywords: Learning Outcomes, Interactive Media, Motivation, PowerPoint